نزاع الصحراء الغربية ومحاولات التسوية مابين الفترة (1988- 2019) - توتو عبد الرحمان مولاي (جامعة محمد بوضياف المسيلة, 2019)
يعتبر نزاع الصحراء الغربية من اعقد النزعات وأطولها إذ تعتبر الصحراء الغربية آخر مستعمرة إفريقية وتصنف ضمن الأقاليم و الخاضعة لتصفية الاستعمار حسب أجندة الأمم المتحدة والاتحاد الإفريقي , وللإحاطة بمختلف جوانب الموضوع تطرقنا في الفصل الأول إلى ذكر بطاقة تعريفية ودراسة بدائية حول القضية منذ جذورها , وكيف تعاقب عليها الاستعمار (من الاستعمار الاسباني إلى الغزو المغربي).على العموم كان الفصل حول الجذور تاريخية للنزاع الصحراء الغربية . ثم دخلنا في صلب الموضوع بالنسبة للفصل الثاني الذي تطرقنا فيه إلى دراسة القضية من جانب المنظمات الدولية والإقليمية وتبين مواقف حول الجوار والدول الكبرى الفاعلة في هذا نزاع مع إظهار تأثيرها على القضية وفيما يخص الفصل الثالث خصصنا للسيناريوهات جل القضية الصحراوية وكيف ساهمت الأمم المتحدة في حل هذا النزاع مع إعطاء البدائل الممكنة لإيجاد حل سلمي دون الرجوع للكفاح المسلح يرضي الطرفين. Abstract : The western sahara is one of the most complex and long _term conflicts.westrensahara is the last African colony and is classified in the regions under the united nations and African unions agenda. In order to examine the various aspects of the subject we discussed in the first chapter a basic card and study on the issue form its roots. Colonialism (from spanich colonization to the Moroccan invasion ). In genral .the chapter on roots. Was historical to the western sahara conflict. Then we entered the heart of the topic for the second chapter in which we discoussed the study of the issue by international and regional organizations andbtwineen the positions of the neighboring countries and major actors in this conflict with the case to show its impact in maikhas chapter lll dedicated to sceniohart the bulk of the Saharawi couse and how the united nations contributed to the resolution of the conflict. Giving possiple alternatives to find a peaceful solution without recourse to the armed struggle of the satisfaction of the parties
Keywords: الصحراء الغربية/ النزاع/ التسوية/1988-2019